(untitled) (Research, Society and Development, 2021)
Transgender persons can be understood as those whose gender identity does not conform to the norms imposed by society regarding the gender designated at birth, based on the genitalia. Obviously, secondary sex characteristics are contingent on sex steroids. Hormonal reassignment has two aims: to reduce the hormonally induced secondary sex characteristics of the original sex and to induce the secondary sex characteristics of the new sex. The use of these sex steroid hormones can favor the development of oral mucosal lesions, such as pyogenic granuloma, which it is a non-neoplastic vascularized lesion, common in the oral cavity, caused by trauma, local irritants, or hormonal factors. The etiology is currently unclear, but trauma and increased level of estrogen and progesterone have been suggested as potential contributing factors. Therefore, the main purpose of this article is to report a pyogenic granuloma developing in a male-to-female transsexual patient which may be associated to the hormonal therapy and highlights the effects of hormone therapy on oral tissues